Acute kidney injury electronic alerts: mixed methods Normalisation Process Theory evaluation of their implementation into secondary care in England - Gregory Maniatopoulos; Tracy Finch; Jason Scott; Mark Bevan; Chris Gibbins; Bryan Yates; Narayanan Kilimangalam; Neil Sheerin; Nigel Suren Kanagasundaram (BMJ Open)
Objective Around one in five emergency hospital admissions are affected by acute kidney injury (AKI). To address poor quality of care in relation to AKI, electronic alerts (e-alerts) are mandated across primary and secondary care in England and Wales. Evidence of the benefit of AKI e-alerts remains conflicting, with at least some uncertainty explained by poor or unclear implementation. The objective of this study was to identify factors relating to implementation, using Normalisation Process Theory (NPT), which promote or inhibit use of AKI e-alerts in secondary care.Design Mixed methods combining qualitative (observations, semi-structured interviews) and quantitative (survey) methods.Setting and participants Three secondary care hospitals in North East England, representing two distinct AKI e-alerting systems. Observations (>44 hours) were conducted in Emergency Assessment Units (EAUs). Semi-structured interviews were conducted with clinicians (n=29) from EAUs, vascular or general surgery or care of the elderly. Qualitative data were supplemented by Normalization MeAsure Development (NoMAD) surveys (n=101).Analysis Qualitative data were analysed using the NPT framework, with quantitative data analysed descriptively and using χ2 and Wilcoxon signed-rank test for differences in current and future normalisation.Results Participants reported familiarity with the AKI e-alerts but that the e-alerts would become more normalised in the future (p<0.001). No single NPT mechanism led to current (un)successful implementation of the e-alerts, but analysis of the underlying subconstructs identified several mechanisms indicative of successful normalisation (internalisation, legitimation) or unsuccessful normalisation (initiation, differentiation, skill set workability, systematisation).Conclusions Clinicians recognised the value and importance of AKI e-alerts in their practice, although this was not sufficient for the e-alerts to be routinely engaged with by clinicians. To further normalise the use of AKI e-alerts, there is a need for tailored training on use of the e-alerts and routine feedback to clinicians on the impact that e-alerts have on patient outcomes.